Retention of Donor T Cells in Lymphohematopoietic Tissue and Augmentation of Tissue PD-L1 Protection for Prevention of GVHD While Preserving GVL Activity - Song, Qingxiao; Nasri, Ubaydah; Nakamura, Ryotaro; Martin, Paul J.; Zeng, Defu (Frontiers in Immunology, 2022)
Allogeneic hematopoietic cell transplantation (Allo-HCT) is a curative therapy for hematological malignancies (i.e., leukemia and lymphoma) due to the graft-versus-leukemia (GVL) activity mediated by alloreactive T cells that can eliminate residual malignant cells and prevent relapse. However, the same alloreactive T cells can cause a serious side effect, known as graft-versus-host disease (GVHD). GVHD and GVL occur in distinct organ and tissues, with GVHD occurring in target organs (e.g., the gut, liver, lung, skin, etc.) and GVL in lympho-hematopoietic tissues where hematological cancer cells primarily reside. Currently used immunosuppressive drugs for the treatment of GVHD inhibit donor T cell activation and expansion, resulting in a decrease in both GVHD and GVL activity that is associated with cancer relapse. To prevent GVHD, it is important to allow full activation and expansion of alloreactive T cells in the lympho-hematopoietic tissues, as well as prevent donor T cells from migrating into the GVHD target tissues, and tolerize infiltrating T cells via protective mechanisms, such as PD-L1 interacting with PD-1, in the target tissues. In this review, we will summarize major approaches that prevent donor T cell migration into GVHD target tissues and approaches that augment tolerization of the infiltrating T cells in the GVHD target tissues while preserving strong GVL activity in the lympho-hematopoietic tissues.